2004
DOI: 10.1381/0960892041590962
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Inferior Vena Cava Filters in Bariatric Surgical Patients – Possible Indications and Technical Considerations

Abstract: Inferior vena cava filter placement is not only feasible and safe for the morbidly obese individual undergoing gastric bypass, but should be strongly considered for patients with risk factors for thromboembolic complications or who experience postoperative complications requiring ICU stay or prolonged immobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Retrievable IVCFs are particularly attractive in bariatric patients because the period of increased risk is relatively short. Several studies have demonstrated the feasibility of retrievable IVCF placement without significant complication [14,[16][17][18]. Gargiulo et al observed a significant decrease in perioperative PE in patients who underwent open gastric bypass with a BMI 55 kg/m 2 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Retrievable IVCFs are particularly attractive in bariatric patients because the period of increased risk is relatively short. Several studies have demonstrated the feasibility of retrievable IVCF placement without significant complication [14,[16][17][18]. Gargiulo et al observed a significant decrease in perioperative PE in patients who underwent open gastric bypass with a BMI 55 kg/m 2 [14].…”
Section: Discussionmentioning
confidence: 99%
“…21 This has been suggested and supported by other studies as well. 2,3 The indications, however, for filter placement, filter type, and management after insertion are controversial, because there has been little prospectively-derived data and only a single randomized clinical trial conducted. 20 According to the findings and recommendations of the Thrombosis Interest Group of Canada (2004), 20 there was no evidence for the benefit of IVC filters in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…This has been supported by other studies noting the safety profile of filters as well as the increased risk for thromboembolic complications in the obese population. 2,3 The literature regarding the natural history of FVL, however, does not seem to support this. The association between FVL and pulmonary embolism (PE) is weak, and although there is an increased risk for thrombosis, there is a paradoxical decreased risk of PE.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7] Super-obese patients, defined as having a body mass index (BMI) Ͼ 50 kg/m 2 , are at increased risk for venous thromboembolism (VTE) due to multiple physical and physiologic factors, with PE rates as high as 28%. 1,25,6,[8][9][10][11][12] The mortality from PE in super-obese patients is reported to be 27% to 75%. 4,6 Current techniques for deep venous thrombosis (DVT) prophylaxis include sequential compression devices, early ambulation, and medical prophylaxis with heparin or low-molecular-weight heparin (LMWH).…”
mentioning
confidence: 99%
“…4 Inferior vena cava (IVC) filters have previously been shown to decrease the incidence of and mortality from PE in bariatric surgery patients. 1,4,6,9,[13][14][15][16][17][18][19][20][21] IVC filters are recommended for those patients with super-obesity, decreased mobility, venous insufficiency, previous thromboembolic event, or hypercoagulability. As BMI increases, visualization of the vena cava becomes more difficult fluoroscopically and eventually becomes suboptimal.…”
mentioning
confidence: 99%